2010
DOI: 10.2146/ajhp090229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiplatelet and anticoagulant medications on the vasoocclusive and thrombotic complications of sickle cell disease: A review of the literature

Abstract: Based on the existing data, sickle cell disease should not be used as an independent indication for treatment with an antiplatelet or anticoagulant medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The potential benefits of antiplatelet medications have long been discussed for SCD; earlier studies to investigate the effects of aspirin, dipyridamole and heparin, however, were inconclusive [36][39]. More recent ongoing trials of antiplatelet agents include those that have employed prasugrel, a P2Y(12) adenosine phosphate (ADP) receptor antagonist that inhibits platelet activation and aggregation, and eptifibatide, an α iib β 3 -integrin antagonist, that has also been used during acute pain episodes [40][43].…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of antiplatelet medications have long been discussed for SCD; earlier studies to investigate the effects of aspirin, dipyridamole and heparin, however, were inconclusive [36][39]. More recent ongoing trials of antiplatelet agents include those that have employed prasugrel, a P2Y(12) adenosine phosphate (ADP) receptor antagonist that inhibits platelet activation and aggregation, and eptifibatide, an α iib β 3 -integrin antagonist, that has also been used during acute pain episodes [40][43].…”
Section: Discussionmentioning
confidence: 99%
“…Other antiplatelet agents such as aspirin/dipyridamole, clopidrogel and ticlopidine have not been studied in acute stroke, although they do have a role for secondary prevention [31,36]. In the specific case of adults with SCD, aspirin, aspirin combined with dipyridamole and ticlopidine have all been evaluated in small studies for the prevention or treatment of pain from SCD without increased bleeding [39], but these agents increase the risk of hemorrhagic stroke in the general population [40]. This may be of additional concern in adults with SCD given limited data that hemorrhagic stroke occurs even more frequently in those with a history of ischemic stroke as children [41].…”
Section: Treatment Of Ischemic Strokementioning
confidence: 99%
“…The most common cause of stroke in SCD patients is large vessel narrowing with superimposed thrombosis, as demonstrated by histopathology studies [15,16]. Additionally, postmortem evaluations of patients with SCD often reveal old and new thrombi in the pulmonary vasculature [26], and thrombosis in sickle cell patients is also associated with avascular necrosis of large joints, leg ulcers, and certain pregnancy complications [15,16]. The hypercoaguable state associated with SCD is thought to be due to abnormalities in the cell membrane of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…The hypercoaguable state associated with SCD is thought to be due to abnormalities in the cell membrane of RBCs. Repeated cycles of sickling and unsickling can lead to exposure of phosphatidylserine, an anionic phospholipid generally restricted to the inner cell membrane of RBCs [15,16,27]. Studies have suggested that this abnormal phosphatidylserine exposure in a subset of RBCs can lead to in vivo activation of coagulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation